Proteomic changes in chicken primary hepatocytes exposed to T‐2 toxin are associated with oxidative stress and mitochondrial enhancement. Issue 21 (1st October 2013) - Mu, Peiqiang; Xu, Ming; Zhang, Lei; Wu, Kaixin; Wu, Jun; Jiang, Jun; Chen, Qingmei; Wang, Lijuan; Tang, Xianqing; Deng, Yiqun
Abstract : T‐2 toxin is a mycotoxin that is toxic to plants, animals, and humans. However, its molecular mechanism remains unclear, especially in chickens. In this study, using 2D electrophoresis with MALDI‐TOF/TOF‐MS, 53 proteins were identified as up‐ or downregulated by T‐2 toxin in chicken primary hepatocytes. Functional network analysis by ingenuity pathway analysis showed that the top network altered by T‐2 toxin is associated with neurological disease, cancer, organismal injury, and abnormalities. Most of the identified proteins were associated with one of eight functional classes, including cell redox homeostasis, transcriptional or translational regulation, cell cycle or cell proliferation, stress response, lipid metabolism, transport, carbohydrate metabolism, and protein degradation. Subcellular location categorization showed that the identified proteins were predominantly located in the mitochondrion (34%) and interestingly, the expression of all the identified mitochondrial proteins was increased. Further cellular analysis showed that T‐2 toxin was able to induce the ROS accumulation and could lead to an increase in mitochondrial mass and adenosine 5′‐triphosphate content, which indicated that oxidative stress and mitochondrial enhancement occurred in T‐2 toxin‐treated cells. Overall, these results characterize the global proteomic response of chicken primary hepatocytes to T‐2 toxin, which may lead to a better understanding of the molecular mechanisms underlying its toxicity.